France between the wars : gender and politics - Reynolds, Siân (Routledge, 1996)
Sian Reynolds challenges the prevailing assumption that women had little influence or power in France during the interwar period. She combines extensive empirical research with revealing insights into France's political history and women's history.
Keywords: Women -- Political activity -- France.; France -- Politics and government -- 1914-1940.; Femmes -- Activité politique -- France.; France -- Politique et gouvernement -- 1914-1940.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; POLITICAL SCIENCE -- Essays.; Politics and government; Women -- Political activity; France; 1914-1940